2011
DOI: 10.1111/j.1467-789x.2011.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs: potential molecular link between obesity, diabetes and cancer

Abstract: Clinicians are routinely challenged in their management of cancer patients because of the complexities of obesity and diabetes that are often found as comorbid conditions. Although attention has been given to optimizing treatment planning for these patients, less attention has been given to manage their obesity and diabetes. This suggests that newer, comprehensive approaches must be developed for the treatment of cancer patients as a 'whole' rather than as a single disease. While the specific pathologies of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 157 publications
(185 reference statements)
0
37
0
Order By: Relevance
“…Interestingly, a number of miRNAs that are associated with obesity have also been implicated in carcinogenesis, and deregulated expression of miRNAs may represent a molecular link between obesity and cancer [23]. Here, we show that a specific miRNA, miR-4443, responds to leptin and insulin treatment in CRC-derived cells and that its impaired regulation may contribute to deregulation of downstream signaling, increased cancer metastasis and worse prognosis in a state of leptin resistance.…”
Section: Introductionmentioning
confidence: 63%
“…Interestingly, a number of miRNAs that are associated with obesity have also been implicated in carcinogenesis, and deregulated expression of miRNAs may represent a molecular link between obesity and cancer [23]. Here, we show that a specific miRNA, miR-4443, responds to leptin and insulin treatment in CRC-derived cells and that its impaired regulation may contribute to deregulation of downstream signaling, increased cancer metastasis and worse prognosis in a state of leptin resistance.…”
Section: Introductionmentioning
confidence: 63%
“…miRNAs are small non-coding RNAs (approx. 22 nucleotides) that modulate mRNA stability and repress post-transcriptional translation by binding to target recognition sequences predominantly located within the 3 untranslated regions of target mRNAs [159][160][161][162] . The 'seed sequence' that spans bases 2-8 of the 5 portion of mature miRNAs essentially dictates what target mRNAs would be regulated by a given miRNA.…”
Section: Microrna-mediated Regulation Of Mitochondrial Dysfunction Anmentioning
confidence: 99%
“…Many studies have shown role of miRNAs in both common [13][14][15][16][17] and rare diseases [18]. For instance, miRNAs have been related to metabolic diseases [19], obesity, diabetes and cancer [20]. In particular, functional relevance of miRNA sequences in human disease is also studied [21].…”
Section: Introductionmentioning
confidence: 99%